Comparative analysis of biofilm community on different coloured substrata in relation to mussel settlement. (12th February 2016) - Li, Yi-Feng; Guo, Xing-Pan; Chen, Yu-Ru; Ding, De-Wen; Yang, Jin-Long
Abstract : Mussels are typical macrofouling organisms in the world. In this study, the interaction between the settlement of Mytilus coruscus plantigrades and bacterial community on coloured substrata was determined. Bacterial communities in biofilms developed on seven coloured substrata were analysed by Illumina Miseq sequencing. The mussel settlement response to coloured substrata with no biofilms was also examined. Flavobacteria, Alphaproteobacteria and Gammaproteobacteria were the first, second and third most dominant groups in seven biofilm samples. The results suggest that the inducing activities of these biofilms on plantigrade settlement varied with coloured substrata and the lowest percentage of settlement was observed on biofilms on the green substratum. High-throughput sequencing showed that bacterial community in biofilms also changed with the substratum colour. No significant difference in the inducing activity on plantigrade settlement was observed between the coloured substrata with no biofilms. Thus, difference in plantigrade settlement response may be correlated to the changes in bacterial community on coloured substrata. This finding extends current knowledge of interaction among mussel settlement and bacterial community variability.